PSYCHOLOGICAL PROBLEMS OF TEACHING ENGLISH TO YOUNG LEARNERS - Axmedova Matluba; Abdullayeva Dilnoza; G'ulomjonova Barchinoy (Ta’lim innovatsiyasi va integratsiyasi, 2023)
In every learning situation or environment,human psychology plays an important role.This article provides information about psychological challenges of teaching foreign language to primery school’s children.Also,many possible solutions will be given to this issue.